Who Needs Sensory Education? - Biswas, Tanu (Studies in Philosophy and Education, 2021)
Customarily, reflections on the need to educate sensory and bodily enactments with the world, take for granted that it is the child who must be educated. However, the educational passage of becoming 'rational' and 'grown up' often leaves the adult divorced from her own embodied self. As part of my engagement with childism (conf. Wall in Ethics in light of childhood, Georgetown University Press, Washington, 2010; The child as natural phenomenologist. Primal and primary experience in Merleau-Ponty’s psychology, Northwestern University Press, Evanston, 2013; Child Geogr, 2019, https://doi.org/10.1080/14733285.2019.1668912) in this article, I ask: Who needs sensory education? In response, I propose that it is adults who need sensory education more than their temporal others (Beauvais, in: Spyrou S, Rosen R, Cook DT (eds) Reimagining childhood studies, Bloomsbury Academic, London, pp 57–74 2018) i.e. children. As Merleau-Ponty has shown, the richness of embodied perception that children experience, is relatively distant for adults (Bahler in Child Philos 11:203–221, 2015; Welsh in The child as natural phenomenologist. Primal and primary experience in Merleau-Ponty’s psychology, Northwestern University Press, Evanston, 2013). The particular lived-experience I reflect on is the sense of temporality. Accompanied by two distinct, yet interconnected examples of encounters with Baby Ole and Captain Duke, I suggest that being-with-children can enable philosophical clearings for adults to re-cognise plural temporalities, as opposed to a singular clock-time perception of Time. (The preposition with is used in the sense of the Norwegian hos or German bei, whereby an adult intentionally positions herself as a guest in a child's world.)